Effect of Size, Content and Shape of Reinforcements on the Behavior of Metal Matrix Composites (MMCs) Under Tension - Paknia, A.; Pramanik, Alokesh; Dixit, A.; Chattopadhyaya, S. (Springer, 2016)
The objective of this research was to investigate the mechanical behavior of metal matrix composites (MMCs) 6061 aluminum, reinforced with silicon carbide particles, under unidirectional tensile loading by finite element analysis. The effects of particle’s shape, size and content on the tensile properties of the composites were studied and compared with each other. In addition, stress and strain distributions and possible particle fracture or debonding were investigated. It was found that, among different shapes, a certain shape of reinforcement particle provided better tensile properties for MMCs and, within each shape category, composites with smaller particle size and higher particle content (20%) also showed better properties. It was also found that when the reinforcement content was 10%, the effects of shape and size of the particles were negligible. Not only interfacial length between the reinforcement and matrix materials, but also state of matrix material, due to the presence of the reinforcement particles, affected the stiffness of the MMCs. In almost all of the cases, except for MMCs with triangular particles, when the stress increased, with the increase in the applied positive displacement, the stress distributions remained unchanged.